Loss of Response to Long-Term Infliximab Therapy in Children with Crohn's Disease - George Alex; Di Simpson; Anthony G. Catto-Smith; Oliver Gouldthorpe (MDPI AG, 2013)
Secondary loss of response (LoR) often precludes further use of infliximab in children with Crohn's disease. Immunomodulators may reduce the incidence of LoR but their combination with infliximab presents safety concerns. We aimed to determine the long-term durability of infliximab response in paediatric Crohn's, effect of immunomodulators on LoR, and secondarily the effect of infliximab on growth. We retrospectively audited patients on maintenance infliximab at a single centre. Data included height and weight, Paediatric Crohn's Disease Activity Index (PCDAI), and immunomodulator use. 71 children (32% female, mean age 14.4 years) had been commenced on maintenance infliximab before July 2011. 89% had been on immunomodulators concurrently with infliximab. LoR occurred in 20 (28%), with a median time to LoR of 4.31 years. LoR was significantly increased in children who did not enter remission (PCDAI ≤ 10) after induction (p < 0.05). LoR occurred more frequently in the 72% who ceased immunomodulators, but this failed to reach statistical significance (p = 0.300). Height and weight SDS improved significantly on infliximab. Infliximab is a durable long-term therapy for paediatric Crohn's refractory to conventional therapy. A large-magnitude increase in the rate of loss of response after immunomodulator cessation was not observed.